(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): How do work factors affect work productivity? Purpose: Theoretical presentation of work factors and practical application at the workplace. Method: In the research, we used a qualitative method based on analytical study. Literature, articles and information were collected, reviewed, and analysed. Results: In the research, we confirm the thesis that companies that nurture work factors become better in the long term in relationships and, as a result, more successful than the competition, as creativity and innovation rise to a higher level due to positive work factors. Organization: The research has a great impact on the organization, because after reviewing the work factors, we proved that the company received information in the field of positive work factors, how important this is for the growth of the company. The key is the support of top management, which must promote positive work factors. Society: Employees can do the most in the area of good relations and innovation. A healthy working environment is the future, so it needs to be emphasized a lot. Because innovative companies survive in the technological boom we are witnessing today. Originality: It is an original contribution to the company based on the literature in the field of positive work factors. Limitations/Future Research: The research was done on the basis of selected literature, articles and information. It is also a fact that only one employee expressed his feelings based on the literature he read. Further research would make sense if we conducted a survey on the topic of work factors in the company and got a comprehensive picture of the work factors within the company.